2024
DOI: 10.1038/s41467-024-47013-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence and vaccine efficacy revealed by immunometabolic analysis of SARS-CoV-2-specific cells in multiple sclerosis patients

Sara De Biasi,
Domenico Lo Tartaro,
Anita Neroni
et al.

Abstract: Disease-modifying therapies (DMT) administered to patients with multiple sclerosis (MS) can influence immune responses to SARS-CoV-2 and vaccine efficacy. However, data on the detailed phenotypic, functional and metabolic characteristics of antigen (Ag)-specific cells following the third dose of mRNA vaccine remain scarce. Here, using flow cytometry and 45-parameter mass cytometry, we broadly investigate the phenotype, function and the single-cell metabolic profile of SARS-CoV-2-specific T and B cells up to 8 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
2
1
0
Order By: Relevance
“…In line with previous studies ( 10 , 31 33 ), we observed pronounced immune cell dysregulation in FTY-treated patients, characterized by reduction of all lymphocyte cell types considered. However, in contrast to a previous study ( 34 ), we also detected a significant reduction in Th2 frequency accompanied by a nominal increase in Th1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with previous studies ( 10 , 31 33 ), we observed pronounced immune cell dysregulation in FTY-treated patients, characterized by reduction of all lymphocyte cell types considered. However, in contrast to a previous study ( 34 ), we also detected a significant reduction in Th2 frequency accompanied by a nominal increase in Th1.…”
Section: Discussionsupporting
confidence: 93%
“…This was seen both by evaluating cell surface activation markers and cytokine secretion, and was evident in all MS groups assessed, particularly in FTY-treated patients. These findings are in line with the premature immunosenescence observed in MS and in patients with other inflammatory conditions ( 10 , 39 , 40 ); it includes thymic involution ( 41 ), telomere length shortening ( 42 ), decline in the adaptive immune response, and an expansion of age-associated B cells ( 43 ), with a possible contribution to neurodegeneration ( 44 46 ). Overall, these changes also cause a concomitant increase in the pro-inflammatory state, a phenomenon known as inflammaging ( 47 , 48 ), and a reduced immune response to vaccination ( 49 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation